PEMBERDAAYAN PEREMPUAN MELALUI KELOMPOK TENUN PEWARNA ALAM OLEH LEMBAGA PENGKAJIAN DAN PEMBERDAYAAN MASYARAKAT (LP2M) - Milla Fadhilah; Hermawati Hermawati; Alkhendra Alkhendra (Universitas Islam Negeri Imam Bonjol Padang, 2019)
Women's economic problems have been discussed for a long time but until now it is still considered important to be discussed. Nagari Tanjuang Bonai, Kec. Lintau Buo Utara, Kab. Tanah Datar is one of the villages that is far from access to progress, for that LP2M as a non-governmental organization feels called to participate in empowering its women's groups. LP2M implements a women's empowerment program through the formation of natural dyes weaving groups. This paper wants to find out the form of women's empowerment and the impact obtained by women through the natural dye weaving group formed by LP2M in Nagari Tanjuang Bonai. Research conducted using qualitative research methods. Data obtained from primary and secondary sources. Data collection techniques used were observation, interviews and documentation. The data obtained were analyzed by qualitative descriptive way by following the steps of data reduction, data presentation, and drawing conclusions. The results of the study showed that: the form of women's empowerment carried out by LP2M in Nagari Tanjuang Bonai namely in the form of weaving activities, providing knowledge about social protection, reproductive health and protection of violence against women and children. The impact of the assistance provided by LP2M to women's groups was the resolution of several problems in the community related to economic, social, and community problems that experienced domestic violence.